Gender Imbalance in Science Disciplines at Kyambogo University of Uganda and Development Implications - Lubaale, Grace (Journal of Science and Sustainable Development, 2022)
Kyambogo University (KyU) is one of Uganda’s nine public universities. Like any other University, KyU is experiencing gender imbalance in science disciplines. This comes with glaring development implications in a country of 34.6 million people, women being the majority. This paper presents results from the study that focused on the nature of gender imbalance in science disciplines at KyU; its causes, development implications, and possible remedies. The study followed a mixed methods approach that combined desk review and in-depth interviews. Documents reviewed produced quantitative data using the checklist while in-depth interviews generated qualitative data that was collected through face-to-face interaction with 42 respondents. Quantitative data was analysed using descriptive statistics while qualitative data was analysed through content analysis. Findings indicate that the nature of gender imbalance in science disciplines is reflected in the admissions and completion; while causes are patriarchy, gender stereotypes, and limited mentorship. The development implications on women and society are in terms of low enrolments, self-esteem, academic staff recruitment, and education returns. The study concludes that gender imbalance in science disciplines at KyU is a reality, socially constructed, and can be deconstructed. In order to enhance gender balance in science disciplines, this study recommends creating science awareness in primary and secondary schools, providing scholarships for females to offer sciences at university, affirmative action through STEM Programme, empower the people at KyU to explore the Gender policy and strengthening the Gender Mainstreaming Directorate while ensuring appropriate gender monitoring and evaluation processes.